(untitled) (International journal of medical sciences, 2026)
Osteoporosis (OP) represents a major health concern in the aging population, characterized by reduced bone mass and deteriorated bone microarchitecture due to estrogen deficiency and impaired calcium metabolism. This experimental study aimed to investigate the morphofunctional effects of organic calcium compounds on bone tissue structure in a rat model of osteoporosis. OP was induced by ovariectomy in white outbred female rats, which were subsequently divided into intact, control, comparison (calcium chloride), and experimental (calcium) groups. Bone samples were examined histologically using hematoxylin and eosin staining after standard fixation and decalcification procedures. Morphological analysis of untreated osteoporotic rats revealed bone rarefaction, trabecular thinning, and signs of osteomalacia. In contrast, administration of calcium demonstrated significant restorative changes, including improved trabecular organization and reduced resorptive activity. These findings suggest that organic calcium in the form of calcium alginate promotes bone tissue regeneration and may serve as an effective therapeutic approach for managing osteoporosis.